STRATIGRAPHY OF THE PALEOGENE OF THE SURKHANDARYA DEPRESSION BY NANNOPLANKTON - Kushakov M.S; Kurbonova M.M.; Toshtemirov Sh. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Zones and subzones’ dissectionstratigrafic of Palaeogene sediments of nannoplankton in Surxandarya is considered in the article.